SOCIAL STUDIES LEARNING MODEL IN THE SMPN 2 OF AMBARAWA PRINGSEWU DISTRICT SCHOOL YEAR 2011/2012 - Muji Winarno; Pargito Pargito; Hendry Susanto (Faculty of Teacher Training and Education, University of Lampung, 2013)
Relies on the standard set forth in PP number 19 year 2005 chapter 1 verse 6, teaching social studies in SMP Negeri 2 Ambarawa be qualified national standards relating to the implementation of learning in the educational unit to achieve competency standards. IPS Learning at SMP Negeri 2 Ambarawa District Pringsewu still learning to implement a single method ekspository the cycle; explain, give examples, ask questions and provide in the classical task. With this method, the teacher trouble to serve various needs and demands of students in learning and difficulty pushing underachieving students to improve achievement learning. The purpose of this study was carried out to find out who has been teaching social studies carried out in the SMP 2 Ambarawa and find the ideal form of learning IPS itself. The research was conducted using qualitative descriptive approach. The population in this study were teachers, students, vice principal of curriculum and IPS SMP Negeri 2 Ambarawa Pringsewu District. Instrument data collectors using your observation, interview and documentation. Analysis of data using the Interactive Analysis Model of Milles and Huberman, through data collection, data reduction, data presentation and conclusion.Results showed teachers of SMP Negeri 2 Ambarawa have analyzed a variety of learning materials to be integrated by topic / theme. Learning model that becomes a mainstay in learning IPS in SMP 2 Ambarawa is a think pair share (TPS), as in the approach the topic / theme for this model students will not only understand the material given, but also provides the opportunity for students to analyze reality in daily life think-day stage, and the most important is learning students to cooperation and solidarity to share the stage in the learning model. IPS learning model that must be implemented by the social studies teacher at SMPN 2 Ambarawa are learning model that promotes the achievement of learning objectives and establish IPS is instilling social skills in students. IPS learning objectives can be achieved with various models of cooperative learning, cooperative learning, but most importantly in the IPS should be oriented learning materials, instilling the values of teamwork, an evaluation (test / quiz), and a group award. Keywords: Social Studies Learning Model